Asuhan Keperawatan Hipertermia pada Anak Tifoid di Ruang Wijayakusuma Atas RSUD Kardinah Tegal - Aurelia, Khairin Wanda; Cahyaningrum, Etika Dewi (Jurnal Sehat Mandiri, 2023)
A systemic acute infectious disease caused by the microorganism Salmonella enterica serotype typhi known as Salmonella typhi (S. typhi) is called typhoid, the symptoms that arise include an increase in body temperature of >37.5oC or called fever. Nursing care that can be provided to reduce body temperature in children with fever is using non-pharmacological therapy by compressing aloe vera. The aim of this research is to develop hyperthermia nursing care for typhoid children in the Upper Wijayakusuma Room at Kardinah Tegal Regional Hospital. The research design is a case study. The results of this research were obtained in An. N, after applying the aloe vera compress for 3 days, the fever decreased, it was seen that on the first day the child had a fever with a body temperature of 37.3oC and decreased on the second day to 36.8oC and on the third day 36.4oC, the conclusion was that the aloe vera compress could reduce the fever in typhoid children. It is hoped that they will be able to implement the interventions that have been carried out, including being able to easily care for family members who have fever.